Estuda da formação de vacância induzida em nanotubos de carbono - Rossato, Jussane (2004)
In this work we have performed the study of the single vacancy and the induced vacancy in carbon nanotubes by first-principles calculations using the SIESTA code, which solves the Kohn-Sham equations via the local density approach. The induced vacancy formation process was simulated by force application which is enough to break the chemical bonds between a carbon atom and its neighbourhood atoms creating a tube with a vacancy and one carbon atom. This study was done for the (8,O) and (13,O) carbon nanotubes. Concerning the eletronic properties, we have studied the gap modification and the band structures. The tube with a single vacancy presents an unoccupied leve1 inside the gap, associated with the vacancy, an the tube with a induced vacancy present two unoccupied levels inside at the gap, associated with the atom and the vacancy. The formation energies for the single vacancy and the induced vacancy, are 5.96 eV and 5.99 eV, respectively, for the (8,O) tube. For the (13,O) tube the corresponding formation energies are 6.26 eV and 6.48 eV. In order to elucidate the intensity and the order o£ the bonds breaking we have studied the applied forces versus displacement of the atom and an analisys o£ the charge densities at the region where the force is applied is presented. This study allow us to conclude that the chemical bond along the tube axis is broken before the others and a 15nN force is necessary.